Perancangan dan Simulasi Penggunaan Pembangkit Listrik Tenaga Surya Atap On Grid Pada Gedung Kuliah dan Laboratorium - Supriyono Supriyono; Purwiyanto Purwiyanto; Sugeng Dwi Riyanto; Ipung Kurniawan (Infotekmesin, 2025)
Indonesia has a large solar energy potential, with an average radiation of 4.5-4.8 kWh/mÂ² every day. Politeknik Negeri Cilacap (PNC) can take advantage of this opportunity to develop a Solar Power Plant. This study examines the possibility of building an on-grid rooftop solar power plant in the Department of Electrical and Mechatronics Engineering. This study uses Homer to simulate the solar power plant design. The parameters discussed are total energy production (kWh/year), renewable fraction, net present cost/NPC (Rp) which is all costs used in construction, both in installation and operation of the solar power plant and Cost of energy/COE (Rp/kWh) which is the cost incurred to produce electrical energy per 1 kWh. The results of the study include an average solar energy at PNC of 4.66 kWh/mÂ²/day. Based on Homer's simulation results, the total energy generated by the solar power plant is 149,056 kWh/year, with 68,599 kWh/year from photovoltaic and 80,457 kWh/year from the PLN grid. The renewable fraction is 44.8%. The NPC is Rp 1,880,000,000, and the CoE is Rp 1,000/kWh.